Antesenden Kepuasan dan Konsekuensi Terhadap Loyalitas Wisatawan Nusantara ke Daya Tarik Wisata Ulun Danu Beratan Tabanan - Susila, I Made Gede Darma; Suardana, I Wayan; Sudiarta, I Nyoman (Jurnal Master Pariwisata (JUMPA); Volume 08, Nomor 02, Januari 2022, 2022)
Ulun Danu Beratan is one of the mascots of the global image of Bali tourism. This can be influenced by the quality of the attraction that makes tourists feel satisfied with their visit and want to visit again. The purpose of this study is to determine the relationship between quality and image on tourist satisfaction and loyalty to tourist attractions directly or indirectly. This study uses a quantitative approach by taking a sample of 100 domestic tourists with an accidental sampling technique. Then the data was analyzed using the SmartPLS version 3.0 software. The results of this study indicate that (1) quality does not affect the loyalty of Nusantara tourists while the image of attractiveness has a significant influence; (2) quality and image affect loyalty; (3) satisfaction affects loyalty; 4) satisfaction partially mediates quality and loyalty; (5) and satisfaction partially mediates image and loyalty of domestic tourists who visit the Ulun Danu Beratan Tourist Attraction. Keywords: Tourist attraction quality, image, satisfaction, loyalty, domestic tourists.